Pengaruh Groundsill Pada Degradasi dan Agradasi Dasar Sungai Winongo (Studi Kasus Simulasi Dengan Sedimen D50) - Q. Ananta; S.B. Lesmana; T. Tahadjuddin; P. Harsanto (Civil Engineering Department, Tadulako University, 2023)
One of the rivers in Yogyakarta with sand as its riverbed material is the Winongo River, which has a high potential for riverbed degradation or agradation. Upstream and downstream of the groundsill construction, respectively, can experience degradation and agradation of sediment transport. In this research, the effectiveness of the MPM, Engelund Hansen, and Laursen Copeland equations on HEC-RAS 6.3.1 is examined in terms of determining the level of overall degradation and agradation of the Winongo River bed. The discharge data used in modeling is in the form of secondary data taken from the 2021 DPUPESDM using two discharge conditions, namely wet discharge (Feb-Mar) and dry discharge (August-Sept). There are 796 cross sections along the river's 41.3 kilometer length, 9 of which are groundsill structures. For all equations, d50 serves as the grain diameter. Based on the results of the simulation, the upstream groundsill frequently agradation while the downstream groundsill tends to degradation. The MPM and Engelund Hansen equations are closer to actual field survey than the Laursen Copeland equation, according to the simulation using the three equations. The nine groundsills on the Winongo River still have the potential to harm the river bank by collapsing the downstream portion of the structure because the condition of degradation in the downstream groundsill is more prevalent than aggradation in the upstream groundsill. Due to the average d50 grain size, it is more likely that models used to predict changes in river bed elevation may degrade